2021
DOI: 10.3171/2020.3.jns193434
|View full text |Cite|
|
Sign up to set email alerts
|

Triple motor mapping: transcranial, bipolar, and monopolar mapping for supratentorial glioma resection adjacent to motor pathways

Abstract: OBJECTIVEMaximal safe resection of gliomas near motor pathways is facilitated by intraoperative mapping. The authors and other groups have described the use of bipolar or monopolar direct stimulation to identify functional tissue, as well as transcranial or transcortical motor evoked potentials (MEPs) to monitor motor pathways. Here, the authors describe their initial experience using all 3 modalities to identify, monitor, and preserve cortical and subcortical motor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 43 publications
2
32
0
1
Order By: Relevance
“…When performing subcortical stimulation in descending motor pathways, the use of a train of multiple highfrequency monopolar stimulation pulses at 250-500 Hz may afford the surgeon similar advantages. In one series, the addition of monopolar stimulation to standard bipolar stimulation for the subcortical regions increased identification of descending motor pathways from 30 to 86.4% (66), similar to Szelényi et al's work which improved sensitivity from 54% using bipolar to 92% using monopolar stimulation (65). As mentioned prior, some have chosen to combine bipolar and monopolar stimulation with concurrent motor evoked potential monitoring, termed "triple motor mapping" (66).…”
Section: Translation To Clinical Practicementioning
confidence: 71%
See 2 more Smart Citations
“…When performing subcortical stimulation in descending motor pathways, the use of a train of multiple highfrequency monopolar stimulation pulses at 250-500 Hz may afford the surgeon similar advantages. In one series, the addition of monopolar stimulation to standard bipolar stimulation for the subcortical regions increased identification of descending motor pathways from 30 to 86.4% (66), similar to Szelényi et al's work which improved sensitivity from 54% using bipolar to 92% using monopolar stimulation (65). As mentioned prior, some have chosen to combine bipolar and monopolar stimulation with concurrent motor evoked potential monitoring, termed "triple motor mapping" (66).…”
Section: Translation To Clinical Practicementioning
confidence: 71%
“…More recent developments include a monopolar technique first described by Taniguchi et al in 1993 that instead uses a train of 5-10 short pulses (10-18 ms) at higher frequencies of 250-500 Hz (63,64). Also known as the "train-of-five, " this technique has been popularized in recent years by Szelényi et al (64) and Bello et al (65), as it has shown higher sensitivity in identifying motor pathways (64,(66)(67)(68) with equal safety and efficacy when compared to bipolar stimulation techniques (69). Some surgeons have chosen to combine both bipolar stimulation, for maximal definitive resolution, with monopolar stimulation, for sensitivity and estimation of distance to motor pathways, to maximize the advantages from both modalities (64,66), and the addition of concurrent motor evoked potential monitoring has been termed "triple motor mapping" (66).…”
Section: Bipolar Vs Monopolar Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nossek et al (17) concluded that subcortical stimulation with a monopolar probe and high-frequency multi-pulse stimulation is the most efficient to identify the CST. Gogos et al (26) reported that subcortical motor pathways were identified in 51 cases (86.4%) with monopolar highfrequency stimulation, but only in 6 patients using bipolar stimulation. Gomez-Tames et al (27) compared monopolar and bipolar stimulation and found that bipolar stimulation could produce more selective activation if the CST was close to the resection border and monopolar stimulation was more robust and more effective for the CST far from the stimulation point.…”
Section: Comparison Of Paired Monopolar and Bipolar Thresholds On The...mentioning
confidence: 99%
“…The monopolar stimulation is preferable for identifying corticospinal tract due to the more radiant electric field properties of monopolar probe compared with the bipolar probe and reported to be effective in insular glioma resections (29,30). Recently, a triple brain mapping method including transcranial, monopolar, and bipolar stimulation has been proposed for locating the motor functional area more accurately (31). As a result, the combined application is considered as superior in preserving motor function and enhancing EOR.…”
Section: Brain Mapping Of Motor and Sensory Functional Areamentioning
confidence: 99%